Molecular Dissection of the Antibody Response: Opportunities and Needs for Application in Cattle - Barroso, Ruben; Morrison, W. Ivan; Morrison, Liam J. (Frontiers in Immunology, 2020)
Improving understanding of the bovine adaptive immune response would equip researchers to more efficiently design interventions against pathogens that impact upon food security and animal welfare. There are also features of the bovine antibody response that differ substantially from other mammalian species, including the best understood models in the human and mouse. These include the ability to generate a functionally diverse immunoglobulin response despite having a fraction of the germline gene diversity that underpins this process in humans and mice, and the unique structure of a subset of immunoglobulins with ‘ultralong’ HCDR3 domains, which are of significant interest with respect to potential therapeutics, including against human pathogens. However, more detailed understanding of the B cell response and the production of an effective antibody response in the bovine is currently hampered by the lack of reagents for the B cell lineage. In this article we outline the current state of knowledge and capabilities with regard to B cell and antibody response in cattle, highlight resource gaps, and summarise recent advances that have the potential to fundamentally advance our understanding of this process in the bovine host.